Interactions of helminths with macrophages: therapeutic potential for inflammatory intestinal disease. (3rd October 2018) - Smith, Hannah; Forman, Ruth; Mair, Iris; Else, Kathryn J.
ABSTRACT: Introduction : Macrophages represent a highly heterogeneous and plastic cell type found in most tissues of the body; the intestine is home to enormous numbers of these cells. Considerable interest surrounds the 'M2 macrophage, ' as it is able to control and regulate inflammation, while promoting tissue repair. Areas covered : As potent inducers of M2 macrophages, intestinal helminths and helminth-derived products are ideal candidates for small molecule drug design to drive M2 macrophage polarization. Several gastrointestinal helminths have been found to cause M2 macrophage-inducing infections. This review covers current knowledge of helminth products and their impact on macrophage polarization, which may in the future lead to new therapeutic strategies. A literature search was performed using the following search terms in PubMed: M2 macrophage, alternative activation, helminth products, helminth ES, helminth therapy, nanoparticle, intestinal macrophages. Other studies were selected by using references from articles identified through our original literature search. Expert commentary : While the immunomodulatory potential of helminth products is well established, we have yet to fully characterize many components of the intestinal helminth product library. Current work aims to identify the protein motifs responsible for modulation of macrophages and other components of the immune system.